Effect of ultraviolet A-induced crosslinking on dentin collagen matrix. Issue 10 (October 2015) - Seseogullari-Dirihan, Roda; Tjäderhane, Leo; Pashley, David H.; Tezvergil-Mutluay, Arzu
Highlights For the first time, we evaluated the inhibitory effect of UVA-induced crosslinking on both MMPs and cathepsin-K. UVA-induced crosslinking was tested in the presence/absence of photosensitizer in terms of the loss of dentin mass, degradation by MMPs and cathepsin-K. The results of the study showed that UVA-induced crosslinking significantly inactivated endogenous proteases of dentin.